A Historical-Mythological Approach To Utopian Thought In Ancient Persia - Seyedeh Leila Taghavi Sangdehi (Migration Letters, 2024)
Sir Thomas More, a humanist thinker and politician of the 16th century, was the first person to write a book by the name of Utopia (no place). Before him, Plato had talked about the ideal society in his book named Republic. Both works were based on founding a desirable, no place and abstract world beyond the existing boundaries of their society. In Iran, since ancient times, utopian thought has been of interest and subject to the development and manifestation of various types in historical, religious, and literary texts of this period. By adopting a descriptive-analytical approach, the present article examines the course of utopian thought in Ancient Persia over the mythological period in an attempt to answer the following question descriptively and analytically: what were the utopian manifestations in the mythological period of Ancient Persia? According to Zoroastrian religious texts, as well as other literary and historical scriptures, the indications of utopian thought in Ancient Persia are manifested in the essence of an ideal king, city, and society. The main characteristics of Utopia of the mythological period are the desire for worldly immortality, an ideal king possessing khvarenah, and also the principle of equality between people and discipline in various affairs. Pardis or the ornate garden is a representation of the ideal city and a manifestation of eternal paradise in the Iranian mind. Zoroastrian religious texts such as Avesta also mention Utopia, but unlike the mythological period, this Utopia is not in the past but a promise to be fulfilled in the future.